Penerapan Mixed Reality Sebagai Sarana Pembelajaran Indera Penglihatan Manusia Menggunakan Teknologi Hologram - Arifaldi Jayaputra; Herman Tolle; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The senses are the tools in the human body that make human beings can know and feel the circumstances or interaction from outside. One senses in humans is most important senses. Learning about the material senses sight already studied since sitting in on lessons of elementary school Science (IPA). In fact, until now there are still many found teachers who still use lecture time to teach, because in fact there are still teachers who have yet to harness the learning media in explaining and giving examples. In the absence of new innovations in helping teaching system will make some students feel the lesson became less attractive and make the students do not pay attention to the lesson. With the technology of mixed reality writers want to help resolve these problems by creating applications of learning about the sense of human vision using a 3D hologram later visualization of the application is expected to be used as a means of learning. Based on the test results the results obtained as a percentage of the usability of 82% which belong to the qualifying well and successfully, then the test results on the effectiveness of using the Wilcoxon Signed Rank Test calculations obtained the value of Asymp. SIG 2 tailed i.e. amounting to a meaningful value of 0.00 Asymp. SIG 2 tailed less than the limit value 0.05 p-value significance which means there is a significant difference in the effectiveness of the application before using and after using applications to knowledge about the sense of vision in humans.